Malaysian government and the legislative approach towards de-radicalization - Omar, Muhamad Fuzi; Ismayatim, Muhammad Asyraf (Yeni Turkiye Strategik Arastirma Merkezi, 2017)
The purpose of this study is to identify the legislative approach taken by Malaysian government in dealing with the issue of de-radicalization especially that involve the radical group. In particular, this study provide the meaning of de-radicalization and explain the contents of those legislative acts like SOSMA, POTA, SMATA, POCA, National Security Council Act and AMLAFTA. The method use for this study is through the content analysis of those acts and the reports about those acts in different publications including the newspapers. The study shows that those acts are employed not only to punish those involve in the radical activities, but as means to prevent and to de-radicalize those already involve in such those activities.